Measuring Teachers’ Motivation Toward Professional Development through Integration of Mobile Technology - Habibullah Pathan; Anna Stepanovna Borisova; Bakhsh, Illahi; Oksana Ivanovna Aleksandrova, (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The integration of technology in teacher training is an integral part of motivation in the 21st century. The integration of mobile technology in teacher training and professional development can bring about a meaningful change in their career. This study examines how, in the academic environment of Sindh, Pakistan, in-service training sessions contribute to the professional skill development and motivation of instructors. The study has two primary aims. The first involved examining how teacher training programs affected instructors’ willingness to continue in the classroom and to enroll in training programs. The second involved examining how these sessions affected teachers’ ability to advance their careers and develop their confidence and self-efficacy. Data for the study were gathered using a survey research approach. To gather information from 450 teachers in Sindh, Pakistan—both private and public—a structured questionnaire was created. The information gathered from the survey was examined using statistical analysis. The study’s findings demonstrate that in-service teachers are not as motivated or proficient in their professional development as they should be by training sessions through the integration of mobile technology. The main motivators for the instructors to attend these workshops are their financial and social advantages. According to the study, several essential elements of successful teacher preparation are absent from these in-service training sessions. As a result, the study suggests that training programs abandon their conventional methods and modernize to better meet the demands of teachers today through the use of technology, which most teachers avoid using. More than merely formal meetings, training sessions should be scheduled to prepare instructors for actual learning objectives. Future academics of teacher training programs may find value in the study’s conclusions with the application of mobile technology by providing appropriate pre-training sessions for the use of technology.